PERBEDAAN HASIL BELAJAR ANTARA GAYA BERPIKIR DIVERGEN DAN KONVERGEN MATA KULIAH GELOMBANG MAHASISWA PENDIDIKAN FISIKA - Ahzan, Sukainil; Gummah, Syifa’ul (IKIP Mataram, 2014)
This study aims to determine differences in student learning outcomes between divergent and convergent thinking styles. The sample of research is the fourth semester students in the Department of Physics Education IKIP Mataram. The experimental design uses a pre-test-post-test one-group design. The data analyzed is the result of cognitive learning and questionnaire of students' thinking character. The research hypothesis was tested by using t test statistic. The result of data analysis can be concluded that there is no difference between learning achievement with convergent and divergent thinking style.